Structural brain correlates of adolescent resilience - Burt, Keith; Banaschewski, Tobias; Flor, Herta; Mann, Karl; Poustka, Luise; Rietschel, Marcella (The journal of child psychology and psychiatry, 2016)
Background Despite calls for integration of neurobiological methods into research on youth resilience (high competence despite high adversity), we know little about structural brain correlates of resilient functioning. The aim of the current study was to test for brain regions uniquely associated with positive functioning in the context of adversity, using detailed phenotypic classification. Methods 1,870 European adolescents (Mage = 14.56 years, SDage = 0.44 years, 51.5% female) underwent MRI scanning and completed behavioral and psychological measures of stressful life events, academic competence, social competence, rule-abiding conduct, personality, and alcohol use. Results The interaction of competence and adversity identified two regions centered on the right middle and superior frontal gyri; grey matter volumes in these regions were larger in adolescents experiencing adversity who showed positive adaptation. Differences in these regions among competence/adversity subgroups were maintained after controlling for several covariates and were robust to alternative operationalization decisions for key constructs. Conclusions We demonstrate structural brain correlates of adolescent resilience, and suggest that right prefrontal structures are implicated in adaptive functioning for youth who have experienced adversity.